The first hostage [large type] : a J. B. Collins novel - Rosenberg, Joel C., 1967- (Center Point Large Print, 2016)
"The American President is missing and presumed to be captured by ISIS while in Jordan. New York Times journalist J. B. Collins and the Secret Service are trying to locate and rescue the President before ISIS's threats become a catastrophic reality"--